Karakteristik Ekstrak Saponin Pada Daun Kucai (Allium schoenoprasum) Asal Pontianak - Widiawati, Helen; Maherawati, Maherawati; Hartanti, Lucky (FoodTech: Jurnal Teknologi Pangan, 2023)
Chives (allium schoenoprasum) is one of the tropical plants grown to harvest the leaves. Chives leaf extract has various health benefits because it contains several phytochemical compounds, namely flavonoids, tannins, triterpenoid, allicin and saponins. Saponin comes from the latin word "sapo" which means it contains stable foam when dissolved in water. The aim was to determine the characteristics of saponins found in chives from Pontianak. The extraction process was carried out using the maceration method with 96% methanol solvent. Analysis of saponin types using LB reagent (Lieberman burchard) and analysis of saponin levels was determined by gravimetric method. The results showed that the types of chives leaf extract saponins were triterpenoid saponins with a brown color and a distinctives odor, with an extract yield of 2,810% ± 0,116, and a stable foam measurement of 2,0 ± 0,2 and saponin levels with an average of 41,941% ± 2,374.